Meningkatkan Kinerja Guru Dalam Menyusun Dan Melaksanakan Program Remedial dan Pengayaan Melalui Supervisi Akademik di SMAN 1 Barru - Akhmad Jamaluddin (Universitas Negeri Makassar, 2021)
The purpose of this research is to improve the ability of teachers to compile and implement remedial and enrichment programs through academic supervision. This research is a school action research that takes place over two cycles with the design of each cycle consisting of four stages namely action planning, implementation, evaluation and reflection. The research subjects numbered 64 teachers with the aim is to improve the performance of teachers / educators in developing and implementing remedial and enrichment programs. The results of the study, in cycle 1, the percentage of the number of teachers who reached the category of very good or good was 53%, not yet reaching the expected teacher performance standard of more than 75%. In cycle 2, the percentage of teacher performance in compiling and implementing remedial and enrichment programs that achieved very good or good has reached 84%. Conclusions, (1) Implementation of academic supervision of supervisors at SMA Negeri 1 Barru can improve teacher performance in preparing and implementing remedial and enrichment programs. This means that if supervisors often carry out academic supervision to teachers, student achievement can improve, this condition indicates that supervision of supervisors is an important variable to consider in improving the school performance.